Die postpandemische Stadt Stadtstrukturen im Stresstest: Zukunftsbilder einer durchmischten und klimagerechten Stadt nach der Pandemie - Bentlin, Felix; Jansen, Hendrik; Kataikko-Grigoleit, Päivi; Million, Angela; Velazco-Londono, Jose M. (Schriftenreihe Städtebau und Kommunikation von Planung, 2021)
How do urban structures change in the post-pandemic city? And what does a global pandemic mean for the city and its people? Until 2020, hardly anyone has probably asked themselves this question. But the sudden changes in public life, with standoff rules and restrictions on movement, have changed the way urban spaces are used. What demands will be placed on urban spaces and structures after the pandemic? To what extent do new forms of organization of everyday life affect urban processes? Findings from university teaching and a national winter school open a critical discussion on urban planning during and after the pandemic. Aspiring planners, architects and designers have expressed their ideas and demands for a mixed-use and climate-friendly city.